2019
DOI: 10.3389/fpsyg.2019.00389
|View full text |Cite
|
Sign up to set email alerts
|

Grit as Predictor of Entrepreneurship and Self-Employment in Spain

Abstract: Extending the growing literature on the role of grit in different life domains, this research explores the relationship between grit and involvement in entrepreneurship. The research highlights the role of personal income and satisfaction with one’s current financial situation as moderators of the relationship between grit and entrepreneurial behavior. Using a large representative sample of Spanish young adults and controlling for a number of potential confounding variables, we find that grit is modestly negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…The other competences identified as critical to the development of entrepreneurial human capital form the grit construct and characterize the so-called grit profile. These competences are considered to be predictors of entrepreneurial behavior (Arco-Tirado et al, 2019), which explains the importance of this group of students. Grit is defined as the maintenance of effort and interest to achieve challenges and long-term objectives (Duckworth et al, 2007), and has a positive relationship with innovation and performance in entrepreneurial environments (Mooradian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other competences identified as critical to the development of entrepreneurial human capital form the grit construct and characterize the so-called grit profile. These competences are considered to be predictors of entrepreneurial behavior (Arco-Tirado et al, 2019), which explains the importance of this group of students. Grit is defined as the maintenance of effort and interest to achieve challenges and long-term objectives (Duckworth et al, 2007), and has a positive relationship with innovation and performance in entrepreneurial environments (Mooradian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Grit is the fuel for entrepreneurship and self-employment (Arco-Tirado et al, 2019), and its two dimensions must therefore be enhanced throughout higher education. Specifically, in relation to young adults, Wolfe and Patel (2016) identify a positive effect of grit in the fostering of self-employment, since the qualities of passion and perseverance contribute to counteract limitations associated with age, such as the difficulty of accessing human, social, and financial resources.…”
Section: Discussionmentioning
confidence: 99%
“…Broad personality traits specifically comprise of the Big Five, which tend to explain broad or general behaviors across different settings ( Loveland et al, 2005 ). To enhance the contribution of personality to understanding entrepreneurship, there have been calls to shift the focus from broad personality traits to narrow ones in predicting entrepreneurial outcome variables since they are likely to be more proximal to behavior ( Obschonka and Stuetzer, 2017 ; Arco-Tirado et al, 2019 ; Obschonka et al, 2019 ). Narrow traits are less broad in their scope and tend to account for greater variance in work related outcomes ( Loveland et al, 2005 ), and hence could be more important to the development of entrepreneurial mindsets and closer to entrepreneurial behaviors ( Rauch and Frese, 2007a , b ; Schmitt-Rodermund et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The meaning of grit is also explained by Butz et al [9] as behavior shown by someone in order to be able to achieve long-term goals by overcoming obstacles and challenges. According to Tirado et al [18], grit is also understood as a striving force that describes a strength in the long run to achieve certain goals despite many obstacles. Duckworth and Quinn [8] designed a measurement to evaluate the grit based on 6 items of perseverance of efforts and 6 items of consistency of interest.…”
Section: Gritmentioning
confidence: 99%
“…Singh and Chopra revealed a strong correlation between grit and intention to work [10]. Specifically, Tirado et al proved that grit acts as a predictor for entrepreneurship and self employment [18]. Therefore, the third and fourth hypotheses are constructed as follows:…”
Section: Hypothesis Developmentmentioning
confidence: 99%